Progressive Supranuclear Palsy (PSP) in the context of Parkinson Plus (Research, Society and Development, 2025)
Introduction: Progressive Supranuclear Palsy (PSP) is a rare neurodegenerative disorder within the Parkinson Plus spectrum, marked by abnormal deposition of tau protein in neurons and glial cells. This primary tauopathy leads to degeneration of the brainstem, basal ganglia, and frontal cortex, resulting in rapidly progressive motor, cognitive, and behavioral symptoms. Its frequently delayed diagnosis underscores its clinical and scientific relevance. Objective: To review the main evidence regarding the pathophysiology, clinical manifestations, diagnosis, and treatment of PSP, contextualizing it among the Parkinson Plus syndromes and highlighting current challenges and future perspectives. Materials and Methods: An integrative literature review was conducted using the PubMed, SciELO, Cochrane, and BVS databases, with the descriptors “Progressive Supranuclear Palsy,” “Parkinson Plus Syndromes,” “Tauopathies,” and “Atypical Parkinsonism.” Articles published between 2005 and 2025 in Portuguese, English, and Spanish addressing clinical, diagnostic, or therapeutic aspects of PSP were included. Results and Discussion: PSP results from abnormal accumulation of 4R tau isoforms, leading to widespread degeneration, particularly in the midbrain. Clinically, it manifests as vertical supranuclear ophthalmoparesis, early axial rigidity, unexplained falls, and frontal cognitive impairment, with poor response to levodopa. Diagnosis is primarily clinical, supported by neuroimaging—especially the characteristic “hummingbird sign.” Treatment is symptomatic and multidisciplinary. Emerging anti-tau therapies show promise but lack robust clinical evidence. Conclusion: PSP is a rapidly progressive tauopathy with a poor prognosis, requiring early diagnosis and integrated management. Understanding its pathophysiology and developing targeted tau-based therapies remain major scientific challenges.